2014
DOI: 10.1161/circoutcomes.113.000527
|View full text |Cite
|
Sign up to set email alerts
|

System Barriers to the Evidence-Based Care of Acute Coronary Syndrome Patients in China

Abstract: 209C hina, a country in the midst of an epidemiological transition, faces many challenges in implementing evidence-based care to curb the growing burden of coronary disease. An aging population and increasing prevalence of cardiovascular risk factors have led to an epidemic of acute coronary syndrome (ACS) across China.1,2 Effective therapies for ACS care, however, continue to be variably used with widespread inequities.3 Furthermore, hospital human resources and adoption of technologies also vary substantiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 43 publications
(52 citation statements)
references
References 28 publications
(35 reference statements)
1
50
1
Order By: Relevance
“…Observational studies, such as Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA Guidelines (CRU-SADE) study, 21 have reported a significant correlation between recommended medication use and in-hospital mortality at the hospital level, suggesting that for each 10% increase in the composite adherence to the American College of Cardiology/American Heart Association guidelines, there was a 10% decrease in the odds of in-hospital mortality by a trend analysis. 20 In our trial, a significant increase in the proportion of patients discharged on recommended therapies was achieved; however, differences in clinical outcomes were not statistically significant. A similar cluster randomized clinical trial (Brazilian Intervention to Increase Evidence Usage in Acute Coronary Syndromes [BRIDGE-ACS] trial) 22 also reported a significant improvement in the use of evidence-based therapies among patients with ACS in Brazil, following a multifaceted educational intervention; however, this study, like ours, had insufficient power to examine hard clinical outcomes.…”
Section: Discussioncontrasting
confidence: 49%
“…Observational studies, such as Can Rapid Risk Stratification of Unstable Angina Patients Suppress Adverse Outcomes with Early Implementation of the ACC/AHA Guidelines (CRU-SADE) study, 21 have reported a significant correlation between recommended medication use and in-hospital mortality at the hospital level, suggesting that for each 10% increase in the composite adherence to the American College of Cardiology/American Heart Association guidelines, there was a 10% decrease in the odds of in-hospital mortality by a trend analysis. 20 In our trial, a significant increase in the proportion of patients discharged on recommended therapies was achieved; however, differences in clinical outcomes were not statistically significant. A similar cluster randomized clinical trial (Brazilian Intervention to Increase Evidence Usage in Acute Coronary Syndromes [BRIDGE-ACS] trial) 22 also reported a significant improvement in the use of evidence-based therapies among patients with ACS in Brazil, following a multifaceted educational intervention; however, this study, like ours, had insufficient power to examine hard clinical outcomes.…”
Section: Discussioncontrasting
confidence: 49%
“…If successful in achieving its primary outcome, then this trial will provide high quality evidence for implementation of this intervention more broadly throughout India and potentially other low- and middle-income countries. Quality improvement is more likely to succeed in the context of longitudinal stakeholder buy-in at multiple levels, including individual, institutional, and organizational;(29,30) we have found the Cardiological Society of India – Kerala chapter to be a vital partner in this research. Whether or not this intervention would be suitable for other acute cardiovascular conditions (e.g., stroke, acute heart failure) remains uncertain but is of interest to our team.…”
Section: Discussionmentioning
confidence: 89%
“…[19,20] During the period, there were also government and non-government quality of care improvement projects taking place, but often without encouraging results. [21] The reasons for this failure may be due, in part, to a lack of knowledge of micro-level hospital management practices and how these practices are linked to the outcomes. Therefore, an objective, easy to apply, standardized method of quantifying hospital management and its relationship with quality of care and clinical outcomes is needed.…”
Section: Introductionmentioning
confidence: 99%